Association Between E-cigarette Use and Depression in US Adults. Issue 5 (September 2020) - Saeed, Omar B.; Chavan, Bhakti; Haile, Zelalem T.
Abstract : Objectives: Electronic cigarette (e-cigarette) use has recently increased among adults in the United States. Previous studies have identified physical health outcomes associated with e-cigarettes. Few studies have examined the relationship between e-cigarette use and mental health outcomes. This study aimed to investigate the relationship between e-cigarette use and depression. Methods: The present cross-sectional study analyzed data from the 2017 Behavioral Risk Factor Surveillance System (BRFSS) in the United States (n = 11918). Results: Overall, 3.7% and 11.2% of the participants were current and former e-cigarette users, respectively. A significantly higher proportion of current e-cigarette users reported having depression (32.4%) than former users (27.3%) and non-users (16.0%). In the multivariable model, we found significant interactions between marital status, employment status, marijuana use and e-cigarette use on depression. Compared to people who do not use e-cigarettes, the odds of self-reported depression were higher among unemployed current e-cigarette users (OR = 2.85, 95% CI = 1.63, 4.97) and unemployed former e-cigarette users (OR = 1.89, 95% CI = 1.26, 2.84). Compared to people who do not use marijuana, the odds of self-reported depression were higher among marijuana users who were also current e-cigarette users (OR = 1.68, 95% CI = 1.08, 2.61) and former e-cigarette users (OR = 1.35, 95% CI = 1.07, 1.71). Compared to people who do not use e-cigarettes, the odds of self-reported depression were higher among widowed/divorced/separated participants who were current e-cigarette users (OR = 3.42, 95% CI = 1.60, 7.29) and former e-cigarette users (OR = 1.55, 95% CI = 1.03, 2.34). Conclusion: In a representative sample of adults in the United States e-cigarette use is associated with depression, predominantly in widowed/divorced/separated, unemployed and people who use marijuana. This association was independent of potential cofounders.